2023
DOI: 10.1073/pnas.2216342120
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small-molecule protein–protein interaction inhibitors for NKG2D

Abstract: NKG2D (natural-killer group 2, member D) is a homodimeric transmembrane receptor that plays an important role in NK, γδ + , and CD8 + T cell-mediated immune responses to environmental stressors such as viral or bacterial infections and oxidative stress. However, aberrant NKG2D signaling has also been associated with chronic inflammatory and autoimmune diseases, and as such NKG2D is thought to be an attractive target for immune intervention. Here, we describe a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…(g) NKG2D (PDB ID: 8EA6) has a binding site for a small‐molecule ligand in the interaction interface of the physiologically functional homodimer (both small molecule and second monomer not shown). Amino acids within 5 Å of the small molecule are colored blue [135] . The small molecule ligand prevents binding of the NKG2D homodimer to endogenous protein ligands containing an α1α2 platform domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(g) NKG2D (PDB ID: 8EA6) has a binding site for a small‐molecule ligand in the interaction interface of the physiologically functional homodimer (both small molecule and second monomer not shown). Amino acids within 5 Å of the small molecule are colored blue [135] . The small molecule ligand prevents binding of the NKG2D homodimer to endogenous protein ligands containing an α1α2 platform domain.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, high‐throughput screenings (HTS) yielded biologically active and chemically tractable lead structures [89,129–131] . Follow‐up studies and mode of action analysis suggested some of these secondary sites to impact CLR function via unprecedented mechanisms, including allosteric modulation of the canonical CBS and changes in quaternary conformation [13,89,130–135] . For instance, a recently identified small molecule ligand was shown to inhibit LOX‐1‐dependent oxLDL uptake by cross‐linking two dimers in a head‐to‐head fashion, sterically blocking the basic spine region, and locking the receptor in an inactive tetramer state (Figure 3c, d and e).…”
Section: Secondary Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The systems used in this work are a combined benchmark dataset from two previous studies. , The Cryptosite set includes 93 apo-holo protein structures, and the PocketMiner set includes 39 apo-holo proteins. We also included a known challenging cryptic pocket from our internal work on natural killer group 2D (NKG2D) in our test set. The Cryptosite set contains more systems with cryptic pockets of different categories.…”
Section: Methodsmentioning
confidence: 99%
“…The NKG2D receptor consists of two disulfide-linked type II transmembrane glycoproteins whose extracellular region contains a C-type lectin-like structural domain [8].…”
Section: Nkg2d and Nkg2d-l 21 Nkg2d Receptormentioning
confidence: 99%